DEMENTIA-SPECIFIC DAYCARE FOR PATIENTS WITH ALZHEIMER'S DISEASE OR RELATED DISORDERS & THEIR CAREGIVERS. (11th November 2018) - Gilbert, K; Gilbert, M; Chiriboga, D; Park, N; Molinari, V
Abstract: Specialized Alzheimer's Adult Day Care Programs are an important part of Home and Community-Based Services (HCBS). Following a tailored intervention approach, Alzheimer's Community Care (ACC) since 1996 has addressed the needs of community-living persons with dementia and their caregivers by providing an innovative multi-service program, centered on 11 dementia-specific day centers, that offers individualized plans of care, assessment, guidance and referrals for caregivers, caregiver support groups, case management services, electronic locator bracelets, and community education. Nearly all of the sample (n=1573+) assessed in the present study had a diagnosis of Alzheimer's disease or a related neurocognitive disorder. Nearly 64% were female, and the average age was over 80.3 years. The majority were non-Hispanic White, but 23% were African American/Black and 16% were Hispanic/Latino. All were nursing home eligible, and over 70% manifest severe cognitive impairment as measured by the Brief Interview for Mental Status (BIMS), a proportion nearly twice that found in nursing home residents. However, over a seven year period an average of only 7.1% unduplicated day center patients were discharged to skilled nursing facilities each year. Only 16% of all those that exited day care were discharged to a skilled nursing facility during the same period. Results suggest the efficacy of full-spectrum services provided to both caregivers and the community-living person they care for.